Authority in Handling Criminal Actions Conducted by Law Enforcers - Yustika Rahmawati; Rosa Linda (Faculty of Law, Universitas Lampung, 2021)
The Corruption Eradication Commission (KPK) was not born. However, the handling of criminal acts of corruption is still not maximal, such as the facts found in the field that currently the eradication of corruption is carried out by the prosecutor's office and the police. The purpose of this research is how the authority regulates corruption in Indonesia and corruption crimes committed by law enforcers. This study uses a normative juridical research method in the form of a literature study, and then the data obtained is descriptive qualitative. The results show that the police carry out the criminal act of corruption in Indonesia as the institution that carries out investigations and investigations, the Attorney General's Office as the institution that carries out the prosecution, and the Corruption Eradication Commission as supervision, which sometimes acts directly as an investigator, investigator, and prosecutor in certain cases. Handling criminal acts of corruption by law enforcers who are tasked with assisting the Corruption Eradication Commission following Article 11 paragraph (1) letter a and Law Number 19 of 2019 concerning the Second Amendment to Law Number 30 of 2002 the Corruption Eradication Commission.